Dexmedetomidine vs. midazolam-ketamine for sedation during awake fiberoptic nasal intubation in patients with difficult airway - A randomized, double-blinded, comparative trial - R Sivakumar; Rashmi Ramachandran; Anjan Trikha; Shailendra Kumar; Bijaya Laxmi; Vimi Rewari (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Both dexmedetomidine and midazolam-ketamine are known for their minimal respiratory depressant effects. While many studies have documented the use of dexmedetomidine in providing conscious sedation during awake fiberoptic-guided nasal intubation (AFNI), the use of midazolam-ketamine combination for this procedure has not been reported. The aim of this study was to compare the efficacy of dexmedetomidine with midazolam-ketamine combination for AFNI in patients with difficult airways undergoing oromaxillofacial surgery. Material and Methods: This study involved 60 patients undergoing oromaxillofacial surgery. They were randomized to receive either dexmedetomidine (1 μg/kg) (group D) or a combination of midazolam (0.02 mg/kg) and ketamine (0.5 mg/kg) (group MK) for sedation during awake fiberoptic nasotracheal intubation. Both groups received topical local anesthesia during the procedure using the spray-as-you-go technique. The primary outcome measured was cough score during intubation. Secondary outcomes included overall intubation, post-intubation, and sedation scores. Incidences of side effects such as hypoxemia and bradycardia were also measured. Results: The cough score (group D: 1.33 ± 0.61, group MK: 1.3 ± 0.53; P = 0.822), overall intubation score, and post-intubation score were comparable between the two groups. Patients receiving dexmedetomidine were significantly more sedated than patients receiving midazolam-ketamine. Patients receiving dexmedetomidine had significantly lower heart rates and blood pressure than patients receiving midazolam-ketamine. Four patients in group D had hypoxemia, while no patient in group MK developed hypoxemia. Conclusions: Both dexmedetomidine and midazolam-ketamine combinations were equally effective for sedation during AFNI in patients with difficult airways scheduled for orofacial maxillary surgery. Patients receiving dexmedetomidine were more sedated, but the incidence of side effects was similar in both groups.